Before Russo-Ukrainian War: How Did EU-Ukraine Association Agreement of 2014 Transform Ukraine’s Economy? - Hakan Erpolat; Nurtaç Yıldırım (Theory, Methodology, Practice, 2024)
In this paper is tried to identify, if exists, any degree of qualitative divergence in Ukraine’s economic structure before and after the EU-Ukraine Association Agreement, and examine whether the agreement fulfilled its promises. The way in which we investigate the issue is by employing ADL modelling, bifurcating the whole model as before agreement model (BAM) and after agreement model (AAM). It’s been observed severe disruptions in the structure of export, import and foreign direct investment, transformed Ukraine’s economy into less favorable position, aggravating the economy’s weak spots. Under these considerations, hypothesis that EU-Ukraine Association Agreement is transformative in the unpromising sense, and it has been of no little effect in building up new and unfavorable economic paradigm for Ukraine is scientifically substantiated.